Error Detection and Correction System (EDAC) of On Board Data Handling (OBDH) in real time operating system behaviour / Haryono ... [et al.] - ., Haryono; Eko Putra, Agfianto; Istiyanto, Jazi Eko; Harjoko, Agus (Research Management Institute (RMI), 2013)
The satellite requires the support of a robust sub system. On Board Data Handling (OBDH) is the core function ofthe satellite subsystem and has to be error free in managing the operation of the satellite. It should withstand the harsh environmental conditions in space that has a lot ofhazards caused by radiations. In view of these two conditions, the OBDH design should be able to manage the operation and overcome the hazards of radiation. In order to manage the operation Real Time Operating System (RTOS) was applied. RTOS was able to manage the task efficiently and effectively. In the aerospace domain, RTOS has become popular because of its strength in managing the operating system. Error Detection and Correction System (EDAC) system was applied to make OBDH more robust. This paper discusses the implementation of the EDAC system in tandem with the RTOS behaviour to manage the operation and increase the robustness of the system. The findings show that OBDH can be programmed successfully using RTOS to handle critical and robust operations.